THE DESIGN THINKING AND THE HEALTH SERVICES: THE COMPETITIVE DIFFERENTIAL THROUGH THE HUMANIZATION OF PATIENT EXPERIENCE - Caulliraux, Adriano Amaral; Meiriño, Marcelo Jasmim (Brazilian Journal of Operations & Production Management, 2015)
It is necessary to rethink the different experiences of patients in health care area. Feelings such as anxiety and fear, for example, are common in the interactions between caregivers and patients, which reflects the disparity between the offered and the necessary to meet the patients’ demands. In this article, there will be analyzed two cases of successful application of the Design Thinking in the Health Care area, the “Mayo Clinic” – elected the best hospital in the USA in 2014 - and the “Humanization of the perioperative experience of the elective patient ” – a Master's thesis developed by the author at Fluminense Federal University (UFF) in 2015. It’s demonstrated the potential of using the Design Thinking for the systematic planning and re-planning of the health service, seeking to meet and transpose the human beings expectations, generating values for the clients, market spread and leveraging a competitive advantage.